KEMENERUSAN VEIN KUBANG CICAU DI BAWAH LEVEL 500 BERDASARKAN ANALISIS KEKAR - -, Ismawan T. (Fakultas Teknik Geologi Universitas Padjadjaran, 2006)
Pongkor area is known as one of the gold mine in Java. With the reserve at present and decreasing each year a new gold reserve must be discovered.Study on structures, especially fractures on Kubang Cicau vein is conducted to discover a possiblity of Kubang Civau vein continuity below level 500.Fractures analyses along the Kubang Cicau veins shows that there are development of intens fracture arround the main vein. Based on structural evaluation result it is recommended that areas between MW1 and MW2, around MW5 and on the south of MW7 can obtain a vein with a sufficient thickness at the level 450.